Proximate analysis, phtochemical screening and antioxidant activity of different strains of ganoderma lucidum (Reishi Mushroom) - Mohammad Azizur Rahman; Abdullah Al Masud; Nilufar Yasmin Lira; Salman Shakil (Open Journal of Biological Sciences - Peertechz Publications, 2020)
In this study, proximate analysis, phytochemical screening and antioxidant activity of two strains of medicinal mushroom Ganoderma lucidum (arbitrarily named strain 5 and 7) and their mix, cultivated in Bangladesh National Mushroom Development Institute, have been determined. The mix was used to determine whether it contains higher nutritive value than strain 5 and 7 alone. Protein content per 100 gm of strain 5, 7 and mix had been found to be 278.85mg, 298.69mg  and 286.19mg, respectively. Lipid content estimated were 2.43gm, 1.96 gm and 2.4gm, respectively, while that of ash were 4.42 gm, 6.11gm and 3.93gm, respectively.  Ganoderma lucidum strain 7 contained highest amounts of total phenol, total flavonoid, ascorbic acid and reducing sugar than the others. Among the three strains evaluated in the present study, G. lucidum 7 contained highest nutritional and medicinal components. Thus, G. lucidum 7 might be an ideal food supplement to the consumers.